Nutritional Status of Kacang Goats Fed Ruminally Undegradable Protein to Improve Their Productivity - Kustantinah, Kustantinah; Indarto, Edwin; Rusman, Rusman; Budisatria, I Gede Suparta; Adiwinarti, Retno (2016)
Kacang goat is one of the local goats in Indonesia that is usually reared by farmers. They are razed during the day and housed at night fed only roughage without concentrate, therefore, their productivity is low. The aim of this study was to improve local goats productivity using aminally undegradable protein (fish meal and soybean meal) in the ration. Twelve Kacang gaits, 1-1.5-year-old, with the initial body weight of 17.84 + 1.57 kg (CV =8.80%) were used ma this study and arranged with a Completely Randomized Design. The goats were fed by 3 afferent rations: TO (control)= natural grass, T1 = Pennisetum purpureum (30%) + Gliricidia leaves (30%) + concentrate with fish meal and T2 = Pennisetum purpureum (30%) + Gliricidia leaves (30%) + concentrate with soybean meal. The ration was made total mixed Nation containing 14% crude protein and 1% of the mineral mix, except for TO. The goats sere fed about 4.5% dry matter ration of the body weight. Water was provided ad libitum. Parameters observed were an average daily gain (ADG), nutrients intake, digestible nutrients, and feed conversion ratio (FCR). Data were analyzed by analysis of variance and Duncan's Multiple Range Test. The ADG of TO (41.57 q) was lower (P<0.01) than that of T1 (72.75 kg) and T2 (91.71 kg), because the DMI/BW" , CP, ether extract and NFE intake of TO was lower (P<0.05) than those of T1 and T2. The ADG of goats were higher in fish meal ration (TI) by 75.01% and in soybean meal ration (T2) by 120.62% over control (TO). The gestible energy conversion and FCR of T1 and T2 were better (P<0.01) than that of TO. It inn be concluded that the use of ruminally undegradable protein (fish meal and soybean meal) in the ration can improve the productivity of Kacang goats.